Effect of Capivasertib in Patients With an AKT1 E17K-Mutated Tumor: NCI-MATCH Subprotocol EAY131-Y Nonrandomized Trial - Kalinsky, Kevin; Hong, Fangxin; McCourt, Carolyn K; Sachdev, Jasgit C; Mitchell, Edith P; Zwiebel, James A; Doyle, L Austin; McShane, Lisa M; Li, Shuli; Gray, Robert J; Rubinstein, Larry V; Patton, David; et al. (JAMA oncology, 2021)
In the National Cancer Institute Molecular Analysis for Therapy Choice (NCI-MATCH) trial, agents targeting genetic tumor abnormalities are administered to patients. In the NCI-MATCH subprotocol EAY131-Y trial, patients with an AKT1 E17K-mutated metastatic tumor received the pan-AKT inhibitor capivasertib. To assess the objective response rate (ORR) of capivasertib in patients with an AKT1 E17K-mutated tumor. Between July 13, 2016, and August 10, 2017, patients in the NCI-MATCH trial were enrolled and assigned to the subprotocol EAY131-Y nonrandomized trial. Patients included adults with an AKT1 E17K-mutated metastatic tumor that had progressed with standard treatment, and these patients were assigned to receive capivasertib. Tumor assessments were repeated every 2 cycles. Data analysis of this evaluable population was performed from November 8, 2019, to March 12, 2020. The study treatment was capivasertib, 480 mg, orally twice daily for 4 days on and 3 days off weekly in 28-day cycles until disease progression or unacceptable toxic effect. If patients continued hormone therapy for metastatic breast cancer, the capivasertib dose was 400 mg. The primary end point was the ORR (ie, complete response [CR] and partial response) according to the Response Evaluation Criteria in Solid Tumors criteria, version 1.1. Secondary end points included progression-free survival (PFS), 6-month PFS, overall survival, and safety. In total, 35 evaluable and analyzable patients were included, of whom 30 were women (86%), and the median (range) age was 61 (32-73) years. The most prevalent cancers were breast (18 [51%]), including 15 patients with hormone receptor (HR)-positive/ERBB2-negative and 3 with triple-negative disease, and gynecologic (11 [31%]) cancers. The ORR rate was 28.6% (95% CI, 15%-46%). One patient with endometrioid endometrial adenocarcinoma achieved a CR and remained on therapy at 35.6 months. Patients with confirmed partial response had the following tumor types: 7 had HR-positive/ERBB2-negative breast cancer, 1 had uterine leiomyosarcoma, and 1 had oncocytic parotid gland carcinoma and continued receiving treatment at 28.8 months. Sixteen patients (46%) had stable disease as the best response, 2 (6%) had progressive disease, and 7 (20%) were not evaluable. With a median follow-up of 28.4 months, the overall 6-month PFS rate was 50% (95% CI, 35%-71%). Capivasertib was discontinued because of adverse events in 11 of 35 patients (31%). Grade 3 treatment-related adverse events included hyperglycemia (8 [23%]) and rash (4 [11%]). One grade 4 hyperglycemic adverse event was reported. This nonrandomized trial found that, in patients with an AKT1 E17K-mutated tumor treated with capivasertib, a clinically significant ORR was achieved, including 1 CR. Clinically meaningful activity with single-agent capivasertib was demonstrated in refractory malignant neoplasms, including rare cancers. ClinicalTrials.gov Identifier: NCT00700882.